Efficient Synthesis by Mono‐Carboxy Methylation of 4, 4′‐Biphenol, X‐ray Diffraction, Spectroscopic Characterization and Computational Study of the Crystal Packing of Ethyl 2‐((4′‐hydroxy‐[1, 1′‐biphenyl]‐4‐yl)oxy)acetate. Issue 32 (26th August 2019) - Khan, Burhan; Khalid, Muhammad; Shah, Muhammad Raza; Tahir, Muhammad Nawaz; Khan, Muhammad Usman; Ali, Akbar; Muhammad, Shabbir
Abstract: Herein, mono‐carboxy methylation of 4, 4′‐Biphenol was accomplished to give ethyl 2‐((4′‐hydroxy‐[1, 1′‐biphenyl]‐4‐yl)oxy)acetate (EBPA ). The chemical structure ofEBPA was determined using single crystal XRD and characterized by FT‐IR, UV‐Visible, 1 H‐NMR, EIMS and elemental analysis. Additionally, computational studies ofEBPA were performed using density functional theory (DFT) at M06‐2X/6‐311+G(d, p) and B3LYP/6‐311+G(d, p) levels of theory to get optimized structures and countercheck the experimental findings. Overall, DFT findings at M06‐2X/6‐311+G(d, p) level show good concurrence with the experimental data which confirms the purity ofEBPA . Frontier molecular orbital (FMO), molecular electrostatic potential (MEP), natural bond orbital (NBO) analysis and nonlinear optical (NLO) properties were explored at M06‐2X/6‐311+G(d, p) level of theory. UV‐Vis analysis at TDDFT/M06‐2X/6‐311+G(d, p) level of theory showed that experimental absorption wavelength was in good agreement with DFT calculated absorption wavelength. NBO analysis disclosed that hyperconjugative interactions and hydrogen bonding network are responsible for the stability ofEBPA . The global reactivity parameters indicate thatEBPA holds more donating capability and stability. The NLO results were observed better than standard molecule recommended the NLO activity ofEBPA . We hope that this synergistic experimental‐computational study may provide new ways for the utilization ofEBPA as NLO material for hi‐tech applications. Abstract : The mono‐carboxy methylation of 4, 4′‐Biphenol has been accomplished to synthesize the ethyl 2‐((4′‐hydroxy‐[1, 1′‐biphenyl]‐4‐yl)oxy)acetate (EBPA ) with chemical formula C16 H16 O4 . The chemical structure ofEBPA was characterized using single crystal x‐ray diffraction and spectroscopic techniques. Additionally, density functional theory (DFT) at M06‐2X/6‐311+G(d, p) level was performed to countercheck the experimental findings and to explore the electronic as well as nonlinear optical (NLO) properties. This synergistic experimental‐computational study may provide new ways for the utilization ofEBPA as NLO material for optoelectronic applications.